A MODEL FOR LOYALTY IN THE CONTEXT OF CUSTOMER RELATIONSHIP MARKETING - Toedt, Michael (European Scientific Journal, ESJ, 2014)
This paper focuses on the effect communication on the sales performance within CRM. The paper uses the hotel business as an example to evaluate if communication within Customer Relationship Management creates loyalty measured by the re-purchase behavior of existing hotel guests. The re-purchase behavior is regarded in the paper as the final outcome of loyalty. In addition the research evaluates the qualitative distinctions between the most common message transmitters in direct marketing, namely e-mail and post mail. Over the last years an increasing number of companies have replaced the costly media channel post mail with the cheaper channel e-mail. This was done without a fundamental knowledge of the effect of switching marketing channels on the sales performance. Different variables are responsible for customer loyalty. The author uses the European Customer Satisfaction Index model (ECSI) to create a new model which describes loyalty from a Customer Relationship Management standpoint. For the quantitative research the marketing actions and bookings of four hotels in Germany were reviewed over a time period of 4.5 years. Due to relatively low marketing budgets hotels rely on direct marketing, therefore the results should also be applicable as a bench mark for other SME’s. The results show a direct correlation between communication and the sales performance. Also a clear qualitative distinction between e-mail and post mail as a message transmitter within CRM could be identified. The outcome should stimulate manager to a re-evaluate their existing communication strategy and should be used as a basis for further research.